2013
DOI: 10.1073/pnas.1305569110
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD47 antibody–mediated phagocytosis of cancer by macrophages primes an effective antitumor T-cell response

Abstract: Mobilization of the T-cell response against cancer has the potential to achieve long-lasting cures. However, it is not known how to harness antigen-presenting cells optimally to achieve an effective antitumor T-cell response. In this study, we show that anti-CD47 antibody–mediated phagocytosis of cancer by macrophages can initiate an antitumor T-cell immune response. Using the ovalbumin model antigen system, anti-CD47 antibody–mediated phagocytosis of cancer cells by macrophages resulted in increased priming o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
464
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(494 citation statements)
references
References 34 publications
12
464
2
1
Order By: Relevance
“…This suggests that F4/80 ϩ CD80 high and F4/80 ϩ MHC-II high activated macrophages further activate CD4 ϩ T cells and/or induce cytokines, which can provide a biased help to the B cells to induce IgG2c isotype antibodies more effectively. In addition, it was reported that macrophages showed increased phagocytosis of cancer cells in the absence of CD47-mediated signaling (43). Interestingly, SIRP␣-Fc treatment interfering with the CD47 pathway was able to reduce Th2-driven allergic airway inflammation (44), a finding which is in line with the results of IgG2c dominant antibody responses in CD47KO mice after i.n.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that F4/80 ϩ CD80 high and F4/80 ϩ MHC-II high activated macrophages further activate CD4 ϩ T cells and/or induce cytokines, which can provide a biased help to the B cells to induce IgG2c isotype antibodies more effectively. In addition, it was reported that macrophages showed increased phagocytosis of cancer cells in the absence of CD47-mediated signaling (43). Interestingly, SIRP␣-Fc treatment interfering with the CD47 pathway was able to reduce Th2-driven allergic airway inflammation (44), a finding which is in line with the results of IgG2c dominant antibody responses in CD47KO mice after i.n.…”
Section: Discussionsupporting
confidence: 77%
“…are sensitive to blocking anti-CD47 antibodies (233,234,(241)(242)(243)(244)(245)(246)(247)(248)(249)(250). This makes CD47 the first protooncogene that is universally expressed in all cancers; its function is known, and blockade of its function is therapeutic.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Themmentioning
confidence: 99%
“…Mouse macrophages incubated with anti-CD47 antibody, which facilitated phagocytosis of human tumors that express cytoplasmic ova as a tumor antigen, cross-present the ova peptide with MHC I to TCR transgenic CD8, but not CD4 T cells in vitro (247). Such macrophages can be used to vaccinate syngeneic mice that have been transfused with OT-I T cells, and will resist subsequent challenge with a mouse leukemia that expresses cytoplasmic ova.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Themmentioning
confidence: 99%
“…For example, blocking of the colony stimulating factor 1 receptor (CSF-1R) in mice with aggressive mammary cancer, reduces pulmonary metastases regulated by macrophages ( Figure 1 ). An alternative approach to this is stimulating macrophages to increase T cell immune response [8] (Tseng et al, 2013). This was done using anti-CD47 antibody, which increased phagocytosis of cancer cells by macrophages and increased priming of CD8 + T cells, accompanied by decreased priming of CD4 + T cells.…”
Section: Macrophages As Drug Targetsmentioning
confidence: 99%